How will ChatGPT affect several business sectors in the future? : a perspective from the education sector - Lopes, Leonor de Sousa e (2024)
ChatGPT is a chatbot developed by OpenAI and launched in November 2022, based on Artificial Intelligence that utilizes the technique of pre-trained generative transformer to provide contextual responses in natural language. This chatbot is built on the "Generative Pre-Trained Transformer" architecture, enabling training a deep network of data from a variety of texts found on the internet. Thus, this model can learn the structures and patterns of human language through this pre-training. ChatGPT is designed to construct natural and relevant conversations, setting it apart from more traditional chatbots. Based on the requests it receives, it can generate responses that are relatively human-like. Furthermore, OpenAI modified ChatGPT using an approach known as "Reinforcement Learning from Human Feedback". This involves training the model with human feedback to enhance its performance and produce significantly more accurate and relevant responses. This study examines the role of ChatGPT, an advanced language model, in the educational sector. It begins with a comprehensive literature review on the use of Artificial Intelligence in education, emphasizing some areas where the chatbot has proven to be effective. These areas include creating educational content, addressing student queries, and even generating assessment material for teachers. Additionally, it analyzes how educators and students utilize ChatGPT, highlighting successes and potential issues. This thesis also discusses ethical issues related to the use of ChatGPT in education, encompassing privacy and reliability concerns and how they may impact student motivation, critical thinking, and learning. In conclusion, ethical and adaptive educational policies are crucial to guide the responsible use of ChatGPT and other technologies in an ever-changing educational environment. The findings contribute to the ongoing discourse about the responsible integration of Artificial Intelligence into educational practices.